The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1021/ja904441a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Regio-, Diastereo-, and Enantioselective Benzylic Allylation of 2-Substituted Pyridines

Abstract: We report a new method for the highly regio-, diastereo-, and enantioselective palladium-catalyzed allylic alkylation of 2-substituted pyridines that allows for the formation of homoallylic stereocenters containing alkyl, aryl, heteroaryl, and nitrogen substituents. When the reaction is conducted with asymmetric acyclic electrophiles, both linear and branched products may be obtained exclusively by selecting the appropriate regioisomeric starting material and ligand, an example of the “memory effect.” Deuteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(44 citation statements)
references
References 19 publications
0
38
0
4
Order By: Relevance
“…In pioneering studies, Trost and co-workers reported the highly enantioselective palladium-catalyzed AAA with 2-methylpyridine derivatives (Scheme 2A, LG=leaving group). [11] Key to success of this approach was addition of 1.3 equiv BF 3 to bind the nitrogen and acidify the sp 3 -hybridized C-H’s of 2-methylpyridine (p K a ~ 34 [12] ). A different strategy is necessary for pronucleophiles bearing less acidic C–H’s in the absence of Lewis basic heteroatoms, such as toluene derivatives (p K a ~ 43 [13] ).…”
mentioning
confidence: 99%
“…In pioneering studies, Trost and co-workers reported the highly enantioselective palladium-catalyzed AAA with 2-methylpyridine derivatives (Scheme 2A, LG=leaving group). [11] Key to success of this approach was addition of 1.3 equiv BF 3 to bind the nitrogen and acidify the sp 3 -hybridized C-H’s of 2-methylpyridine (p K a ~ 34 [12] ). A different strategy is necessary for pronucleophiles bearing less acidic C–H’s in the absence of Lewis basic heteroatoms, such as toluene derivatives (p K a ~ 43 [13] ).…”
mentioning
confidence: 99%
“…12j Notably, acceleration of palladium catalyzed reactions of pyridine derivatives by addition of Lewis acids has been described by Nolan, 14 Hartwig, 15 and Trost. 16 Other workarounds include use of substrates with directing groups, such as 2-(2-pyridyl)acetic acids, 12h 2-(2-pyridyl)ethanols, 12b pyridine N -oxides, 12d, 12f and N -iminopyridines. 12e We previously used 2-benzyl pyridine (p K a = 28.3–28.7 in THF), where the benzylic hydrogens are estimated to about 6 orders of magnitude more acidic than those in 2-picoline (p K a = 34 in THF).…”
Section: Resultsmentioning
confidence: 99%
“…Successful strategies to circumvent this potential problem include addition of Lewis acids to bind the pyridyl nitrogen and increase the reactivity of the benzylic C–H's 12 j . Notably, acceleration of palladium catalyzed reactions of pyridine derivatives by addition of Lewis acids has been described by Nolan,14 Hartwig,15 and Trost 16. Other workarounds include use of substrates with directing groups, such as 2-(2-pyridyl)acetic acids,12 h 2-(2-pyridyl)ethanols,12 b pyridine N -oxides,12d,12f and N -iminopyridines 12 e .…”
Section: Resultsmentioning
confidence: 99%
“…[38] Die Reaktion eines racemischen Substrats mit einem einzelnen Enantiomer des Katalysators erzwingt die Bildung beider diastereomerer h 3 -Cyclohexenyl/ Pd-Intermediate über komplementäre und unkomplementäre Ionisationsereignisse. [38] Die Reaktion eines racemischen Substrats mit einem einzelnen Enantiomer des Katalysators erzwingt die Bildung beider diastereomerer h 3 -Cyclohexenyl/ Pd-Intermediate über komplementäre und unkomplementäre Ionisationsereignisse.…”
Section: Regioselektivitätunclassified